Reproductive Tract Mucus May Influence the Sex of Offspring in Cattle: Study in Cows That Have Repeatedly Calved Single-Sex Offspring - Fei Huang; Peng Niu; Jieru Wang; Jiajia Suo; Lulu Zhang; Jie Wang; Di Fang; Qinghua Gao (Veterinary Sciences)
This study aimed to investigate the selective effect of the reproductive tract mucus in cows that have consistently produced offspring of a single sex on X/Y spermatozoa. We collected mucus from the reproductive tract of cows that had given calvings to offspring of the same sex, or alternated between sexes, for more than five consecutive calvings. We evaluated the pH of reproductive tract mucus. Subsequently, we conducted a spermatozoa penetration assay; the proportions of X and Y spermatozoa after penetration were then identified by dual TaqMan qPCR and flow cytometry. This was followed by in vitro fertilization and embryo sex determination experiments. Immediately afterwards, computer-aided spermatozoa analysis was employed to analyze the spermatozoa that had penetrated through different types of mucus in the reproductive tract. The analysis indicated that the reproductive tract mucus of cows consistently producing male or female calves exhibited selectivity towards X/Y spermatozoa. The differences in the pH values of the reproductive tract mucus among cows continuously producing male calves, those continuously producing female calves, and those alternately giving birth to male and female calves were not significant (p ≥ 0.05). The outcome of dual TaqMan qPCR for cows consistently producing male calves was Y: 79.29 ± 4.28% vs. X: 21.67 ± 4.53%; for cows consistently producing female calves, the equation was Y: 25.05 ± 4.88% vs. X: 75.34 ± 5.13%. The results of flow cytometry processing revealed the following proportions: for cows consistently producing male calves: Y: 83.33 ± 5.52% vs. X: 17.23 ± 4.74%; for cows consistently producing female calves: Y: 24.81 ± 4.13% vs. X: 76.64 ± 4.21%. The outcomes of embryo sex determination for cows consistently producing male calves were as follows: male embryos vs. female embryos (79.60 ± 2.87% vs. 21.07 ± 2.51%); for cows consistently producing female calves, the outcomes for male embryos vs. female embryos were 25.58 ± 3.96% vs. 75.63 ± 3.55%. Computer-aided analysis revealed that the concentration of spermatozoa penetrating the reproductive tract mucus in cows alternating between male and female calves (9.09 ± 0.72 million/mL) was significantly higher than that in cows consistently producing male calves (6.01 ± 1.19 million/mL) and cows consistently producing female calves (5.61 ± 0.60 million/mL). There were no significant differences in spermatozoa motility, the proportion of progressive motile spermatozoa, and curvilinear, straight-line, and average path velocities. Collectively, these findings indicate that the reproductive tract mucus of cows consistently producing offspring of a single sex exhibits selectivity towards either X or Y spermatozoa. This finding is of great significance for studying the impact of maternal factors on offspring sex.